MITOLOGI DALAM HIKAYAT MERONG MAHAWANGSA [Mythology in Hikayat Merong Mahawangsa] - Chyntia Dyah Rahmadhani; Asep Yudha Wirajaya (Kantor Bahasa Provinsi Maluku, 2020)
The study commented about Hikayat Merong Mahawangsa: The Salasilah Negeri Kedah Darulaman. Hikayat Merong Mahawangsa consists of five chapters that showed the lineage of Merong Mahawangsa and the founder of Kedah. The problems in this study are(1) Which events were categorized as myth in Hikayat Merong Mahawangsa?; (2) how those myths appeared in Hikayat Merong Mahawangsa?; (3) How is the difference in the depiction of events occurring between Hikayat Merong Mahawangsa and Merong Mahawangsa films? The research aimed (1) to mention the events that could be classified as myths in the Hikayat Merong Mahawangsa; (2) to bring out the events which was the myth; (3) to describe the differences of delination of events that occured in both Hikayat Merong Mahawangsa and Merong Mahawangsa films. This research used qualitative descriptive method of research becauseresearchers intend to describe and interpret all events in Hikayat Merong Mahawangsa and film Merong Mahawangsa as detail without changing the actual state. The manuscript that used as the source of data in this research was the Hikayat Merong Mahawangsa: The Salasilah state of Kedah Darulaman with script number MS134 collection from the Digital Library of Malay Manuscript. Penelitian ini mengulas tentang Hikayat Merong Mahawangsa: Salasilah Negeri Kedah Darulaman. Hikayat Merong Mahawangsa terdiri atas lima bab yang mengisahkan tentang silsilah keturunan Merong Mahawangsa dan pendiri Kedah. Permasalahan dalam penelitian ini, yaitu (1) Apa saja peristiwa yang dapat dikategorikan mitos dalam Hikayat Merong Mahawangsa?; (2) Bagaimana peristiwa-peristiwa mitos bermunculan dalam Hikayat Merong Mahawangsa?; (3) Bagaimana perbedaan penggambaran peristiwa yang terjadi antara Hikayat Merong Mahawangsa dan film Merong Mahawangsa? Penelitian ini bertujuan untuk (1) Menyebutkan peristiwa-peristiwa yang dapat digolongkan sebagai mitos dalam Hikayat Merong Mahawangsa; (2) Memunculkan peristiwa-peristiwa dan kejadian-kejadian dalam Hikayat Merong Mahawangsa yang merupakan mitos; (3) Mendeskripsikan perbedaan penggambaran peristiwa yang terjadi antara Hikayat Merong Mahawangsa dan film Merong Mahawangsa. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif karena penulis bermaksud menjabarkan dan menginterpretasikan peristiwa-peristiwa yang diceritakan dalam Hikayat Merong Mahawangsa dan film Merong Mahawangsa secara detail tanpa mengubah keadaan yang sesungguhnya. Naskah yang digunakan sebagai sumber data dalam penelitian ini merupakan naskah Hikayat Merong Mahawangsa: Salasilah Negeri Kedah Darulaman dengan nomor naskah MS134 koleksi dari Digital Library of Malay Manuscript.